1977
DOI: 10.1002/macp.1977.021780112
|View full text |Cite
|
Sign up to set email alerts
|

Free radical polymerization of unconjugated dienes, 15. Dependence of the composition of poly(methacrylic anhydride) on the monomer concentration

Abstract: The free radical polymerization of methacrylic anhydride in chloroform solutions was investigated at different temperatures. By employing statistical analysis of the experimental data, it could be shown that in all the cases the dependence of the mole fraction of cyclic structural units on the monomer concentration, at which the polymer has been obtained, is in agreement with a kinetic relationship generally valid for the free radical cyclopolymerization of symmetrical unconjugated dienes. *I Part 14: cf. Makr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[3][4][5][6][7] For example, it has been shown that the cyclopolymerization of acrylic anhydride (AA) produces both five membered and six membered rings, while MAA exclusively produces six membered rings during polymerizations conducted up to 80 °C. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] An additional and notable feature of the anhydride-containing MAA and AA diene monomers is that the anhydride moieties are able to undergo dynamic covalent exchange (DCE), which leads to the rearrangement of the polymer structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] For example, it has been shown that the cyclopolymerization of acrylic anhydride (AA) produces both five membered and six membered rings, while MAA exclusively produces six membered rings during polymerizations conducted up to 80 °C. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] An additional and notable feature of the anhydride-containing MAA and AA diene monomers is that the anhydride moieties are able to undergo dynamic covalent exchange (DCE), which leads to the rearrangement of the polymer structure.…”
Section: Introductionmentioning
confidence: 99%
“…3–7 For example, it has been shown that the cyclopolymerization of acrylic anhydride ( AA ) produces both five membered and six membered rings, while MAA exclusively produces six membered rings during polymerizations conducted up to 80 °C. 8–22…”
Section: Introductionmentioning
confidence: 99%